Quality of care of oncological patients with home parenteral nutrition: research - Schneider, Andrea; Baur, Christina; Zopf, Yurdagül; Török, Helga Paula; Sina, Christian; Prinz, Christian; Mönnich, Heike; Madisch, Ahmed; Maluck-Schölecke, Susen; Rötzer, Ingeborg; Seipt, Claudia; Götte, Anja; et al. (Supportive care in cancer, 2024)
Transferring adult cancer patients from the hospital to the home environment for home parenteral nutrition (HPN) can be challenging. There is limited real-world data on how those affected perceive this situation. Our aim was to assess the quality of life (QoL) on HPN and the benefits and burdens from the cancer patient's perspective.
Gesehen am 22.04.2025